Significance of Galectin-3 and N-terminal pro B-type natriuretic peptide in the prediction of atrial fibrillation after cardiac surgery: Biomarkers and post-operative atrial fibrillation - Mladenovic, Nikola; Zdravkovic, Ranok; Velicki, Lazar; Drljevic Todic, Vanja; Todic, Mirko; Maletin, Srdjan; Mladenovic, Aleksandra; Petrovic, Nemanja; Okiljevic, Bogdan; Nikolić, Valentina; Pavlovic, Milan; Krtinic, Dane; et al. (Journal of Medical Biochemistry, 2023)
Background: Post-operative atrial fibrillation (POAF) is a frequent complication after cardiac surgery. It is associated with prolonged hospital stay, increased morbidity, mortality rate and economic costs. The aim of the study was to determine the association between the values of Galectin-3 and N-terminal pro-B-type natriuretic peptide (NT-proBNP) with POAF after cardiac surgery.Patients and methods: A prospective study enrolled patients aged 18-85 years old admitted due to elective coronary artery bypass graft surgery (CABG) or CABG + aortic valve replacement. The plasma Galectin-3 and NT-proBNP levels were measured one day before surgery postoperative days 1 and 7.  Results: The study included a total of 103 patients. POAF was registered in 45 patients. The mean age of patients in whom POAF occurred was 68.8 years, while other patients’ mean age was 65.5 years (p=0.028). Patients with POAF did not differ from the group without POAF in the values of Galectin-3 and NT-proBNP preoperatively as well as on the first and seventh postoperative days. Changes in Galectin-3 levels on the first postoperative day had statistically significant value for predicting POAF (AUC=0.627 [0.509-0.745], p
Keywords: Post-operative atrial fibrillation; Cardiac surgery; Galectin-3; NT-proBNP